Revisión Documental: la Lengua de Señas Colombiana como estrategia de inclusión en la educación superior y las incidencias en las habilidades sociales de personas no oyentes en el siglo XXI (2021)
The present investigation arose due to the increase in exclusion and desertion in recent years in which the deaf community in Colombia is immersed in terms of education, thus bringing a deficit in their social skills. Therefore, this documentary review aimed to analyze the current state of research on the implementation of Colombian Sign Language in Higher Education as an inclusion strategy and the impact on Social Skills of non-hearing people throughout the 21st century. From a documentary review, with a quantitative approach, descriptive scope and empirical-analytical epistemological criteria.